AXBOROT KUTUBXONA MARKAZILARI TOʻGʻRISIDA - Soatova Farog‘at Xolmat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Information Library Centers (ILCs) are integral to modern information systems, serving as hubs that combine traditional library functions with advanced information technologies. Their primary purpose is to provide users with easy and quick access to a wide range of resources, including printed books, scientific articles, electronic databases, and multimedia content. ILCs support educational and research processes by offering necessary materials and facilitating scientific inquiries. In addition, they organize cultural and academic events, contribute to digital archiving, and preserve knowledge for future generations. The modern ILC is a key player in promoting intellectual and cultural development through accessible, efficient, and diverse information services.